Exploring the Use of Justice Reinvestment: Perceptions of Victims Service Providers and the Promise of Reinvestment - Wentling, Richard L. (Victims & offenders, 2023)
Victim Service Providers (VSPs) operate on limited budgets, which constrain their ability to provide adequate services and ensure victims’ needs are met. As such, victims may suffer undue consequences as the result of their experiences with crime. In order to increase VSPs’ efficacy, and improve outcomes for victims, sustainable funding sources need to be identified. The justice reinvestment initiative (JRI) is a federally funded program promoting practices within state-level criminal justice policies to reduce prison populations and improve funding for community-based services. A recurring aspect of the JRI legislation is focused on providing support and funding opportunities for VSPs; however, the extent to which VSPs can access JRI funding to support their programs remains largely unknown. This exploratory study sought to assess VSPs familiarity with JRIs as a source of funding. Results suggest that VSPs are potentially missing out on funding opportunities due to a lack of knowledge of the funding that reinvestment strategies present. Furthermore, the bureaucratic delivery of JRI may obscure it’s potential as a funding source from VSPs. This study suggests that improvements need to be made to streamline JRI funding sources and increase VSPs and other agencies’ access to the resources provided by JRI policies.